Monts d’Australie, espaces des mythes, des quêtes, des déchirements - Colette Selles (Anglophonia)
From Ayers Rock (Uluru) to Tasmanian mountains, this article focuses on real and symbolic spaces. It aims at underlining the existential, spiritual dimension of the perception and representation of the Australian landscape traditionally associated with Aboriginal people, and which stands in stark contrast with the colonial enterprise characterized by violation and exploitation. However, a more harmonious future is suggested with visions of rebirth, regeneration and plenitude in the Tasmanian highlands